Self-esteem Modulates the P3 Component in Response to the Self-face Processing after Priming with Emotional Faces - Guan, Lili; Zhao, Yufang; Wang, Yige; Chen, Yujie; Yang, Juan (Frontiers in Psychology, 2017)
The Self-face Processing Advantage (SPA) refers to the research finding that individuals generally recognize their own face faster than another’s face; self-face also elicits an enhanced P3 amplitude compared to another’s face. It has been suggested that social evaluation threats could weaken the SPA and that self-esteem could be regarded as a threat buffer. However, little research has directly investigated the neural evidence of how self-esteem modulates the social evaluation threat to the SPA. In the current event-related potential (ERP) study, twenty-seven healthy Chinese undergraduate students were primed with emotional faces (angry, happy or neutral) and were asked to judge whether the target face (self, friend, and stranger) was familiar or unfamiliar. Electrophysiological results showed that after priming with emotional faces (angry and happy), self-face elicited similar P3 amplitudes to friend-face in individuals with low self-esteem, but not in individuals with high self-esteem. The results suggest that as low self-esteem raises fears of social rejection and exclusion, priming with emotional faces (angry and happy) can weaken the SPA in low self-esteem individuals but not in high self-esteem individuals.